Interaction between coal and lignin briquettes in co-carbonization. (15th September 2022) - Koskela, Aki; Suopajärvi, Hannu; Fabritius, Timo
Highlights: Hydrolysis lignin and lignin chars, pyrolyzed were co-carbonized with coking coal. L1200 did not have joint interface with coke structure after co-carbonization. The coke structure near the HLIG and L450 briquette was found to be highly porous. Voids were formed between the coke and the structure of the chars, L600 and L1200. Voids were related to dilation and contraction of the chars in the coking process. Abstract: The utilization of bio-based side streams in metallurgical coke making promotes two major factors in the mitigation of climate impact in the steel industry. Circular economy as the waste material from biorefinery industry is utilized as a raw material in the steel industry, and mitigation of the production of fossil-based CO2 emissions. In this work, lignin from the hydrolysis process was used in a briquetted form as part of the raw material blend in metallurgical coke making. For the experiments and analyses, lignin briquettes were pyrolyzed at 450, 600 and 1200 °C, while one sample was left non-pyrolyzed. In the co-carbonization of briquetted lignin, lignin chars and bituminous coal, the focus was to evaluate the interaction between char and coal in the carbonization. This was studied by thermogravimetric analysis (TGA), optical dilatometry, and light optical microscopy. The results suggested that the interaction between the coal and lignin reduced when the pyrolysis temperature of the briquettes, prior to co-carbonization, was elevated. This was due to the decrease of overlapping of the pyrolysis rates of chars and coking coal. Combined with the dilation and shrinking behaviour of the chars, presented in this paper, separate char and coke structures were formed in the final coke in co-carbonization.